The Influence of Talent Management, Job Satisfaction, and Retention on Employee Performance - Ariyanto, Ricky Alfian; Robbie, R. Iqbal; Roz, Kenny; Pratika, Yeyen (Jambura Science of Management, 2025)
Purpose: The purpose of this research is to determine and analyze talent management, job satisfaction, employee retention and employee performance, the influence of talent management on employee performance, the influence of job satisfaction on employee performance, the influence of talent management on employee retention, the influence of job satisfaction on employee retention, the influence employee retention on employee performance, employee retention can mediate the influence between talent management on employee performance and employee retention can mediate the influence between job satisfaction and employee performance.Design/Methodology/Approarch: The type of research in preparing this thesis is explanatory research with the population, namely, production employees at PT. Polowijo Gosari Gresik, namely 234 employees, with a sample size of 70 respondents. The data analysis technique uses a range of scales and Structural Equation Modeling (SEM) with the partial least squares (PLS) method.Findings:  The research results show that talent management is included in the good criteria, job satisfaction is quite satisfactory, employee retention is good, and employee performance is quite high. Talent management does not affect employee performance, job satisfaction has an effect on employee performance, talent management has no effect on employee retention, job satisfaction has no effect on employee retention, employee retention has an effect on employee performance, employee retention is unable to mediate the effect of talent management on employee performance and employee retention is unable to mediate the influence of job satisfaction on employee performance.